Recent advances in nonlinear analysis : proceedings of the International Conference on Nonlinear Analysis, Hsinchu, Taiwan, 20-25 November 2006 - Chipot, M. (Michel); Lin, Chang-Shou; Tsai, Dong-ho (World Scientific, 2008)
This volume considers the most recent advances in various topics in partial differential equations. Many important issues such as evolution problems, their asymptotic behavior and their qualitative properties are addressed. The quality and completeness of the articles make this book both a source of inspiration and reference for future research.